Workshop Menumbuhkan Minat Baca dan Penanganan Kesulitan Membaca Anak di Perumahan Graha Indah Samarinda - Hikmah, Nurul (Dharma: Jurnal Pengabdian Masyarakat, 2021)
In this global era, the world of education is increasingly advanced and developing. Education is one of the references for assessing a country. A country can be said to be developing if it is seen from the education index and the number of illiterates of a country. Humans must adopt a culture of reading. By using the senses of sight and hearing, humans can get the information contained in the objects they "read" from books, newspapers, magazines and television. Reading interest is influenced by external and internal factors. The purpose of this activity is to provide guidance and understanding to the community (parents and children) about the importance of fostering interest in reading books and handling reading difficulties in children; Assisting the University in formulating policies, plans and programs related to community service activities, whether carried out by lecturers or students; Apply and develop science; as well as collaborating in the field of community service. However, there are still some obstacles, namely mothers need mentoring facilities, such as mobile libraries and sustainable tutors for their children. The targets of this community service program are to foster interest in reading, improve reading skills and help deal with reading difficulties in children. Based on the observations, it can be seen that the service activities that have been carried out can be said to be quite successful. This was shown by the positive response from mothers and children who enthusiastically participated in the workshop until it was finished. This workshop activity has been carried out. With 30 participants, consisting of parents and children. This community service is in the form of a workshop or gradual guidance consisting of the planning, preparation, implementation and evaluation stages. This activity is carried out with face-to-face events and reading practices that go well and smoothly.